Loss of H3K27me3 imprinting in the Sfmbt2 miRNA cluster causes enlargement of cloned mouse placentas - Kimiko Inoue (Nature Portfolio, 2020)
Somatic cell nuclear transfer (SCNT) frequently results in abnormal placenta development in cloned mice. Here the authors show that loss of histone methylation (H3K27me3) imprinting in clustered Sfmbt2 miRNAs contributes to SCNT placenta defect.